Aerosol Optics: light absorption and scattering by particles in the atmosphere - Kokhanovsky, Alexander, A. (Springer, 2017)
The area of aerosol research is extensive. Therefore, no attempt has been made toachieve a comprehensive coverage of the results obtained in the area to date. The main focus of this book is the theoretical basis of the aerosol optics. The results presented are very general and can be applied in many particular cases. The first section is concernedwith the classification of the different aerosol particles existing in the terrestrial atmo-sphere with respect to their chemical composition and their origin (e.g., dust and sea salt aerosols, smoke, and biological and organic aerosols). In the second chapter, I intro- duce the chief notions of aerosol optics, such as absorption, scattering, and extinction coef- ficients, and also phase functions and scattering matrices. Numerous examples of single scattering calculations using Mie theory are presented. Chapter 3 aims to describe tech-niques for the calculation of multiple scattering effects in aerosol media. The results are of importance for studies of light propagation in thick aerosol layers, where the single scat-tering approximation cannot be used. The discussion in this section is based on the solid ground of radiative transfer theory. Both scalar and vector versions of the theory are pre-sented. Chapter 4 is focused on the Fourier optics of aerosol media. In particular, the re- duction of contrast due to atmospheric effects and also the optical transfer functions of aerosol media are considered in detail. This section is of importance for understanding image transfer through the terrestrial atmosphere. The final chapter of the book is focused on the application of optical methods for the determination of aerosol microphysical and optical properties. Such topics as measurement of both direct and diffused solar light using Sun photometers and satellite remote sensing of atmospheric aerosol are covered. Also lidar measurements from ground and space are briefly touched upon in this chapter.